Analysis of statistical data on drop collisions in an aerosol flow during experiments; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 196 : Actual Problems of Thermal Physics and Physical Hydrodynamics - Antonov D. V. Dmitry Vladimirovich; Vysokomornaya O. V. Olga Valeryevna; Piskunov M. V. Maksim Vladimirovich; Shlegel N. E. Nikita Evgenjevich (2019, 2019)
Title screen